Optimization of electro-strain and ferroelectric properties of P(VDF-TrFE) films under the synergistic effect of PTO nanosheets and in-situ electrostatic field - Kaiqi Zhu; Fu Lv; Jiamin Lin; Zijian Hong; Yongjun Wu; Yuhui Huang (Journal of Materiomics)
Traditional ferroelectric materials, such as lead zirconate titanate (PZT) ceramics, exhibit positive strain when subjected to an electric field along the polarization direction. In contrast, the piezoelectric polymer polyvinylidene fluoride (PVDF) and its copolymer P(VDF-TrFE) display unique negative strain properties. While extensive research has focused on understanding the origin and mechanisms of this negative strain, limited efforts have been directed toward regulating these properties. This study optimizes the electro-strain and ferroelectric properties of P(VDF-TrFE) piezoelectric films through the synergistic effect of PbTiO3 nanosheets and an in-situ electrostatic field. Our results demonstrate that while the incorporation of PbTiO3 nanosheets does not notably enhance ferroelectricity, it significantly improves electro-strain properties, particularly negative strain, which increases from −0.097% to −0.185%, an enhancement of 91%. Moreover, the ferroelectric polarization and positive strain of P(VDF-TrFE) are further enhanced under the combined influence of PbTiO3 nanosheets and in-situ electrostatic field, increasing maximum polarization from 10.79 μC/cm2 to 13.16 μC/cm2, a 22% improvement, and positive strain from 0.213% to 0.267%, a 25% enhancement. We propose a possible mechanism for these improvements, attributed to the enhanced flexibility of the amorphous phase and increased content of polar β-phase in P(VDF-TrFE) films under this synergistic effect. This work highlights novel strategies for controlling the electro-strain and ferroelectric properties of P(VDF-TrFE) piezoelectric films.